2020
DOI: 10.1002/cbf.3531
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA FAM66C is associated with clinical progression and promotes cell proliferation by inhibiting proteasome pathway in prostate cancer

Abstract: Prostate cancer is the most prevalent malignancy in men, and the identification of novel oncogenes is clinically valuable for early screening, prevention and treatment. Recently, the studies have revealed that long non-coding RNAs (lncRNAs) play important roles in the development and progression of cancers including prostate cancer. The present study aims to identify a novel lncRNA that correlated with the survival time of prostate cancer patients and try to explore its biological functions in prostate cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…LncRNAs and miRNAs have also been found to play a regulatory role in the growth, metastasis and progression of ICC, such as lncRNA MNX1‐AS1, 14 lncRNA CCAT1, 15 and lncRNA SNHG3 16 . The previous study showed that lncRNA FAM66C promotes proliferation via the inhibition of the proteasomal pathway in prostate cancer 17 . The lncRNA FAM66C (hereinafter referred to as FAM66C, Gene ID: HSALNG0089050) is located on chromosome 12 with 46 243 nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs and miRNAs have also been found to play a regulatory role in the growth, metastasis and progression of ICC, such as lncRNA MNX1‐AS1, 14 lncRNA CCAT1, 15 and lncRNA SNHG3 16 . The previous study showed that lncRNA FAM66C promotes proliferation via the inhibition of the proteasomal pathway in prostate cancer 17 . The lncRNA FAM66C (hereinafter referred to as FAM66C, Gene ID: HSALNG0089050) is located on chromosome 12 with 46 243 nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…FAM66C decreased expression following activation may be linked to the need for antibody secreting cells to have an active and functioning proteasome pathway to remove excess unfolded Ig molecules. Thus, this ncRNA has been shown to be associated with inhibiting the proteasome pathway in prostate cancer [59]. The lncRNA MATN1-AS1 has been shown to inhibit proliferation in the context of glioblastoma due to its ability to inhibit expression of RELA [60].…”
Section: Discussionmentioning
confidence: 99%
“…MIR210HG is also identified as a prognostic lncRNA in glioma ( 60 ), hepatocellular carcinoma ( 61 ), and colorectal adenocarcinoma ( 62 ). FAM66C is not much reported compared to the above lncRNAs, but it is illustrated to promote cell proliferation by suppressing proteasome pathway in prostate cancer, promote cancer progression in cholangiocarcinoma and pancreatic cancer ( 63 65 ). MYCNOS also functions as an oncogenic role in promoting GBM cell proliferation and hepatocellular carcinoma invasion ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%